A rare case of ectopic parathyroid cyst associated with Hashimoto thyroiditis - Claudia Alexandrina Irimie; Mihai Stelian Vârciu; Andreia Loredana Găitănar; Marius Irimie (Journal of Clinical and Translational Endocrinology Case Reports, 2021)
Introduction: Parathyroid cyst is a rare parathyroid disorder and represented <1% of cervical masses. Intrathyroidal parathyroid cyst are rare conditions with only few cases reported. Depending on their ability to secrete parathyroid hormone (PTH), PC can be divided into functioning and nonfunctioning. Clinical case: We present a case of 34-year-old women presenting with an asymptomatic anterior neck mass. The ultrasonography of the neck revealed a cystic transonic image, larger than 30 mm, delimited by a thin echogenic wall in the right thyroid lobe. Fine-needle aspiration of the mass revealed a clear, translucent, watery fluid, appearance suggestive for a parathyroid cyst. Intact PTH measured in fluid cyst revealed a high level of 208 pg/mL (normal ranges 10–69 pg/mL), consistent with our presumptive diagnosis. Intact parathyroid hormone serum level was 24 pg/mL. Serum levels of calcium and phosphorous were 9.9 mg/dL and respectively 2.9 mg/dL. Anti-thyroid peroxidase (anti-TPO) antibodies were in high titer indicating chronic autoimmune thyroiditis. Diagnosis of ectopic nonfunctional parathyroid cyst associated with Hashimoto thyroiditis was established by ultrasound-guided FNA and measurement of cystic fluid PTH level. Conclusion: Parathyroid cyst is an uncommon benign neck lesion that should be considered in the differential diagnosis of a neck mass and ultrasound-guided FNA of cystic fluid with assay for PTH level is an effective method of differentiating parathyroid cyst from thyroid cyst.